Current knowledge on the velvet ants (Hymenoptera: Mutillidae, Myrmosidae) of Vietnam: faunal review and new distributional records - Okayasu, Juriya; Lelej, Arkady S.; Williams, Kevin A.; Brabant, Craig M.; Nguyen, Lien Thi Phuong; Nguyen, Anh Duc; Pham, Thai Hong; Truong, Tuong Thi Cat (Zootaxa, 2025)
Tropical and subtropical regions of East Asia harbor enormous yet undiscovered diversity of velvet ants. Nevertheless, continental Southeast Asia has been less intensively studied compared to Northeast Asia and islands of the Pacific Ocean. In this paper, the velvet-ant fauna of Vietnam is reviewed based on primary literature and specimens obtained in recent field surveys and from various museum collections. Before this study, fifty species were recorded, mostly from the northern provinces. Here, we examined 734 specimens and the following twenty-seven species are newly recognized from this country: Pherotilla brothersi Zhou, Lelej & Xu, 2017 (Rhopalomutillinae), Hemutilla bifurcata (Chen, 1957), H. granulata Tu, Lelej & Chen, 2014 (Sphaeropthalminae), Bischoffitilla malica (Zavattari, 1914), B. mammallifera (Chen, 1957), B. perakensis (Pagden, 1934), B. tumidula (Mickel, 1933) (Myrmillinae), Kurzenkotilla harmandi (André, 1898) (Mutillinae: Mutillini), Andreimyrme davidi (André, 1898), Mickelomyrme exiloides (Magretti, 1892), M. isora (Cameron, 1900), M. puttasoki Williams, 2019, Promecilla decora (Smith, 1879), P. levinaris (Chen, 1957), Sinotilla ansula (Chen, 1957), S. hong Lelej, 1995, S. trisecta (Chen, 1957), Smicromyrme thaochani Williams, 2019 (Mutillinae: Smicromyrmini), Krombeinidia chang Williams, 2019, Kr. meeungensis (Cockerell, 1928), Neotrogaspidia recticarinata (Chen, 1957), Orientidia thoawanae Williams, 2019, Pagdenidia hymalajensis (Radoszkowski, 1885), Promecidia abnormis Lelej, 2016, Trogaspidia wilsoni Williams, 2019, Wallacidia retinula (Chen, 1957) (Mutillinae: Trogaspidiini), and Zeugomutilla pangi Lelej, 2017 (Mutillinae: Zeugomutillini). Additionally, 169 new provincial records are presented. As a supplement to the previously published works, specimen-based records are provided for the species recorded without reference to voucher material. Taxonomic history, geographic distribution, sex association, seasonal occurrence, and habitats are reviewed for all 77 species in 29 genera. The number of known species from each province was greatly variable, and 46.0% of the 63 provinces currently have no recorded velvet ants. Twenty-five of the 77 recorded species are described from both sexes. Hosts are known for only two species. These data highlight the need for intensive field surveys, specifically in the southern provinces, to elucidate the true biodiversity of velvet ants in this country, which is likely even higher than what is documented here.